2019
DOI: 10.1038/s41427-019-0185-z
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive liposomes loaded onto an injectable, self-healing and antibacterial hydrogel for promoting bone reconstruction

Abstract: Loading hydrogels with bioactive agents is an important method for expanding the functional application of hydrogels. However, how to improve the local administration and slow release of drugs from a hydrogel is a challenge when using hydrogels loaded with drugs. In this paper, we first developed adhesive liposomes (A-LIP) loaded with BMP-2. Then, we incorporated the A-LIP into PEG hydrogels based on the coordinated cross-linking principle of SH-PEG and Ag + , fabricating an injectable, antibacterial and self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“…The system could be used for the treatment of bone cavity damage and reduces the risk of postoperative infections. The presence of silver ions in the adhesive liposome PEG gel system showed effective inhibition of S. aureus and E. coli pathogens [73].…”
Section: -Liposomes-hydrogel Systemmentioning
confidence: 99%
“…The system could be used for the treatment of bone cavity damage and reduces the risk of postoperative infections. The presence of silver ions in the adhesive liposome PEG gel system showed effective inhibition of S. aureus and E. coli pathogens [73].…”
Section: -Liposomes-hydrogel Systemmentioning
confidence: 99%
“…This system showed good potential for the repair of the local damaged bone cavity. [ 126 ] However, the A‐LIP released by A‐LIPPEG markedly increased the relative fluorescence intensity (100 ± 20%) as an indicator of osteocalcin (OCN) expression (green), whereas LIP‐PEG and control groups exhibited very weaker fluorescence intensity (46 ± 8%, and 4 ± 1%, respectively), indicating high potential of A‐LIPPEG for enhancement of the osteogenic differentiation of BMSCs (Figure 9F). The assessment of bone healing by micro‐CT scans demonstrated that mineralization and the healing of the fracture in the A‐LIP‐PEG treatment group were greater than the control and LIP‐PEG groups (Figure 9G).…”
Section: Multiple Therapies For Ih‐mediated Tissue Regenerationmentioning
confidence: 99%
“…Staphylococcus aureus bacteria as a mouse model of skin infection Release of carboxyl-modified gold nanoparticles onto mouse skin [ 210] Adhesive cationic liposomes containing lecithin, cholesterol, and octadecylamine Ag + loaded thiolated polyethylene hydrogels Liposomes (A-LIP) loaded with bone morphogenetic protein 2 Local bone remodeling of osteoporotic fractures in rats [ 211] Polymersomes of the triblock copolymer PNAM-b-PChA-b-PNAM PVA hydrogel matrix C2C12 mouse myoblast cell line Release of the small cytotoxic depsipeptide drug thiocoraline [ 272] Polymersomes of the triblock copolymer PMOXA-b-PDMS-b-PMOXA…”
Section: Polyacrylamide Gelsmentioning
confidence: 99%
“…[210] This preparation sustained nanoparticle release within 24 h, without producing any toxic effect on the mouse skin within a 7-day treatment. Another recent demonstration of antibacterial applications is provided by the recent example of Liu et al, [211] who loaded octadecylamine grafted liposomes into Ag + loaded thiolated polyethylene hydrogels, obtaining an interesting system, which combines good self-healing with excellent antibacterial properties (tested on S. aureus and Escherichia coli) thanks to the presence of Ag + .…”
Section: Hydrogel-based Formulationsmentioning
confidence: 99%